2012
DOI: 10.1589/jpts.24.475
|View full text |Cite
|
Sign up to set email alerts
|

Vastus Medialis: a Reappraisal of VMO and VML

Abstract: Abstract.[Purpose] The morphology and innervation pattern of the vastus medialis (VM) were investigated to determine if there was an anatomical distinction between the oblique (VMO) and longus (VML) parts. [Subjects and Methods] Forty lower limbs were dissected. The innervation pattern was observed in 39 specimens. Muscle length and fibre angles of 14 specimens were recorded.[Results] In 22 specimens there was a distinct separation between the VML and VMO (change in fibre angle, fibrofascial plane, vasculature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
3
14
0
Order By: Relevance
“…Previous studies have found average VMO angles ranging from 47 to 57 in cadaveric knees (Weinstabl et al, 1989;Nozic et al, 1997;Farahmand et al, 1998;Peeler et al, 2005;Skinner and Adds, 2012). Ultrasound studies on mildly active nonpathological individuals found an average VMO angle of 56.6 degrees (Engelina et al, in press) and 57.6 (Jan et al, 2009) with a weak positive correlation between VMO angle and insertion ratio.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have found average VMO angles ranging from 47 to 57 in cadaveric knees (Weinstabl et al, 1989;Nozic et al, 1997;Farahmand et al, 1998;Peeler et al, 2005;Skinner and Adds, 2012). Ultrasound studies on mildly active nonpathological individuals found an average VMO angle of 56.6 degrees (Engelina et al, in press) and 57.6 (Jan et al, 2009) with a weak positive correlation between VMO angle and insertion ratio.…”
Section: Introductionmentioning
confidence: 96%
“…Numerous cadaveric studies have been carried out to determine the architecture of the VMO, focusing on the fiber angle, insertion ratio, and location (e.g., Lieb and Perry, 1968;Peeler and Anderson, 2007;Skinner and Adds, 2012). However, there is still uncertainty as to how these results are related to patella tracking in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Most investigations deal primarily with the distal part of the VM, which is also termed vastus medialis obliquus (VMO) (Fig. 6) [3,14,26,40,46,48,50,53]. We were not able to find a separate innervation to the different sections of VM, nor a clearly distinct fascial plane between the two heads.…”
Section: Discussionmentioning
confidence: 80%
“…There have been three reports in the literature of an unusual variant found in cadaveric specimens in which the VMO and VML are incontrovertibly separate entities, as the VML ran deep to a distal and superficial VMO, so that the VMO existed as a separate layer, superficial to the VML. This variation has been reported in 5 out of 22 cadaveric lower limbs5 ) , three out of “more than a hundred” dissected lower limbs3 ) , and bilaterally in one out of a sample of 200 Nigerian cadavers, which the authors called an “accessory quadriceps femoris muscle”4 ) . As far as we are aware, there have thus far been no reports of this unusual variation in living patients encountered in clinical practice.…”
Section: Discussionmentioning
confidence: 95%